2012
DOI: 10.7314/apjcp.2012.13.11.5353
|View full text |Cite
|
Sign up to set email alerts
|

Immunotherapeutic Approach for Better Management of Cancer - Role of IL-18

Abstract: Interleukin-18 (IL-18) is an immune-stimulatory cytokine with antitumor activity in preclinical models. It plays pivotal roles in linking inflammatory immune responses and tumor progression and is a useful candidate in gene therapy of lymphoma or lymphoid leukemia. A phase I study of recombinant human IL-18 (rhIL-18) in patients with advanced cancer concluded that rhIL-18 can be safely given in biologically active doses to patients with advanced cancer. Some viruses can induce the secretion of IL-18 for immune… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 78 publications
1
17
0
Order By: Relevance
“…Conversely, Kuppala et al . showed that IL-18 was an immune-stimulatory cytokine with antitumor activity in preclinical models, and could be a useful candidate in gene therapy of lymphoma or lymphoid leukemia26. The physiological roles of IL-37, a newly identified IL-1 family member, in tumors, were unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, Kuppala et al . showed that IL-18 was an immune-stimulatory cytokine with antitumor activity in preclinical models, and could be a useful candidate in gene therapy of lymphoma or lymphoid leukemia26. The physiological roles of IL-37, a newly identified IL-1 family member, in tumors, were unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Systemic administration of IL-18 has been shown to result in a significant antitumor immune activity in several preclinical animal models. 70 The ɣ-chain family of cytokines includes IL-2, IL-4, IL-7, IL-9, IL-15, and IL-21. IL-2 is a key growth factor involved in the clonal expansion of antigen-activated lymphocytes and the generation of immune memory.…”
Section: Cytokines and Chemokinesmentioning
confidence: 99%
“…It is synthesized as a 24-kDa precursor protein, cleaved into an 18-kDa mature form by caspase-1, and then secreted (3). IL18 is produced mainly by immune cells and effectively enhances innate and adaptive immune responses (4).…”
Section: Introductionmentioning
confidence: 99%